Estudo de caso: o sindicato formando o professor - Câmara, Ramon Mattos (Universidade Federal de São Carlos, 2020)
This paper has, as goal, to analyze, discuss and investigate the contributions of the syndicate in the teachers’ political formation; it compounds the professional development of teachers from the Elementary Education, acting in the state’s networking in São Paulo, in the city of São Carlos. In order to achieve this goal, two instruments to collect data were used: theorical upbringing about the politics and its consequences towards education; documental analysis about the syndicate that the teachers are part of; and semi-structured interviews with the state’s representant from the same syndicate. With the data obtained, we were able to identify that the policy has two dimensions: the first is about the society’s organizational dimension and the second is about the attribution of value in inter-personal relations. The teachers’ political conscience is imperative so that the syndicate might develop its work, thus, also, it is important to be sure about the approximation that the education has with the politics and its consequences in society. The data from the field search indicate that the syndicate acts with political formation proposes to the political formation from a non-formal-intentionally-structured education with meetings and debates in the entity, as much as in different syndicate’s actions that provoke the teachers regarding the education’s social situation. The contributions of these forming actions may help, not only the commitment in the social movements’ mobilizations, but also to comprehend the politics about the teaching profession, about the possibilities of social change and, besides, to contribute in the students’ formation to be citizens.
Case study: the sindicance forming the teacher
Keywords: Formação docente; Profissão docente; Educação básica; Política; Sindicato; Teaching formation; Teaching profession; Elementary education; Politics; Syndicate; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO